Histone demethylase PHF8 drives neuroendocrine prostate cancer progression by epigenetically upregulating FOXA2 - Liu, Qiuli (John Wiley & Sons, Ltd, 2020)

(untitled) (J Pathol)
Neuroendocrine prostate cancer (NEPC) is a more aggressive subtype of castration‐resistant prostate cancer (CRPC). Although it is well established that PHF8 can enhance prostate cancer cell proliferation, whether PHF8 is involved in prostate cancer initiation and progression is relatively unclear. By comparing the transgenic adenocarcinoma of the mouse prostate (TRAMP) mice with or without Phf8 knockout, we systemically examined the role of PHF8 in prostate cancer development. We found that PHF8 plays a minimum role in initiation and progression of adenocarcinoma. However, PHF8 is essential for NEPC because not only is PHF8 highly expressed in NEPC but also animals without Phf8 failed to develop NEPC. Mechanistically, PHF8 transcriptionally upregulates FOXA2 by demethylating and removing the repressive histone markers on the promoter region of the FOXA2 gene, and the upregulated FOXA2 subsequently regulates the expression of genes involved in NEPC development. Since both PHF8 and FOXA2 are highly expressed in NEPC tissues from patients or patient‐derived xenografts, the levels of PHF8 and FOXA2 can either individually or in combination serve as NEPC biomarkers and targeting either PHF8 or FOXA2 could be potential therapeutic strategies for NEPC treatment. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.